Quality of Categorized Service and Customer Satisfaction in Banking Industry: An Empirical Study on Private Commercial Banks in Bangladesh - Masukujjaman, Md; Akter, Afia (Journal of Business and Technology (Dhaka), 2012)
The main objectives of the study are to evaluate the customer satisfaction of the service quality and to assess whether bank services provided by the institutions are satisfactory to Bangladeshi customers especially in term of service categories like general banking, credit banking and foreign exchange banking services. The study also examines empirically the determinants of service quality in Bangladesh. A questionnaire for such purpose was designed and different statistical methods were applied to analyse the collected data. From the study it is found that the overall service quality in private commercial bank in Bangladesh is moderate, where service quality in general banking services is better than the credit banking services and foreign exchange services though its quality is not too bad . In addition, top ranked banks have high service quality in all categories of services and the lower raked banks are struggling seriously with credit and foreign exchange services. So, as policy recommendation, the banks especially the lower ranked banks should give more emphasis on both the credit and foreign exchange banking services. Key Words: Categorized Service; Perceived Service Quality; Customer Satisfaction. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9933 Journal of Business and Technology (Dhaka) Vol. 5(2), July-December, 2010 19-37